LAJU SERANGAN KUMBANG AMBROSIA XYLEBORUS SP. PADA DOLOK TUSAM (PINUS MERKUSII) - Paimin Sukartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
The effect af some treatments of freshly cut Sumaura pine logs (Pinus merkusii) on the rate of ambrosia beetle attack (Xylebarus sp.) was observed. The results showed that:l . Most of the tested logs were initially infested by the beetles about one week after felling.2.There was no significant difference among the susceptibility of any sections of the tree trumk, whether they were teaken from the bottom, middle or top portions.3. Debarked logs were more susceptible, at least in the first week. to the beetle attack.4. Keeping the logs in the shady areas. and also sprinkling with water, may lengthen the period of Jog freshness, but it also means praviding suitable host for the beetles continuausly.